Sequential hemodynamic assessment in aortic valve insufficiency in rats - Koike,Marcia Kiyomi (2014)
OBJECTIVE: In animal models of aortic insufficiency, the right common carotid artery is typically used to damage valve leaflets; this strategy impedes subsequent assessments of left ventricular hemodynamics. The present study aimed to establish an alternative technique that would allow subsequent left ventricular catheterization to monitor sequential hemodynamics in rats with aortic insufficiency. METHOD: The right internal and external carotid artery branches were dissected. The internal branch was temporarily occluded. The external branch was also occluded, and the proximal, patent segment was catheterized. Via the catheter, ventricular hemodynamic evaluations were performed before and after incurring leaflet damage. The catheter was removed, and the right external branch was permanently ligated. The temporary right internal carotid occlusion was released, and blood flow was re-established. After four weeks, left ventricular hemodynamic measurements were performed from the right common carotid artery. RESULTS: Four weeks after the establishment of aortic insufficiency, left ventricular hemodynamic parameters showed a classic chronic hemodynamic pattern, similar to that observed in patients with chronic or compensated aortic insufficiency. Systolic blood pressure was elevated and pulse pressure was increased. CONCLUSION: This new method of carotid artery catheterization permitted two sequential, distinct hemodynamic measurements, in experimental model of aortic valve insufficiency.